Islamic Work Ethics: The New Direction for Research - Gustiawan, Willson (MENARA EKONOMI, 2015)
Much of work ethic research has been carried out in the West, focusing on ProtestantWork Ethic (PWE) as advanced by Max Weber who relate Protestantism and capitalism.There was not much research on Islamic work ethics but a few authors whose work hascontributed towards promoting and highlighting Islamic work principle inorganizational studies. The emersion of Islamic Work Ethic (IWE) is a response to theissue of religious values relation to economic, management and business, that hasbecame popular since decades. This paper is the review paper of some articlesregarding Islamic Work hics. We emphasize on research of IWE, begining with IWEresearch periodization and trend, and how it will develop in the future. The importantconceptual framework was discussed are about effort, competition, tranparency, andmorality. We also compare between IWE and PWE to construct specific IWE. Wepropose new paradigm for future study. This is the last part of two papers on IWE. Wehope this paper can enrich discourse in work ethic literature and encourage futureresearch development.Keyword: Islamic Work Ethic (IWE), PWE, research development on work ethic